bricolage 9 Migrantische Arbeitswelten in Südtirol - Reckinger, Gilles; Reiners, Diana; Zinn, Dorothy (Innsbrucker Zeitschrift für Europäische Ethnologie, 2017)
The present volume presents the results of a four-semester Euregio teaching research project of the Universities of Innsbruck and Bolzano, which ethnographically focused on the everyday working and living conditions of so-called migrants in South Tyrol. The contributions paint a multifaceted picture of the structural difficulties, disadvantages and disabilities that migrants face. In dealing with the surrounding legal conditions and an ethnically and sexually segmented labor market, the volume's contributions ask about biographical breaks and upheavals. At the same time, the case histories show which creative forces, self-empowerment and resistance potentials are developing social actors and how they play an active role in South Tyrolean society.